The role of job stress and job satisfaction in predicting job burnout of teachers of students with special needs - Alamdarloo, Ghorban Hemati; Mohsenifar, Zahra (Penerbit Universiti Kebangsaan Malaysia, 2023)
The aim of this study was to determine the role of job stress and job satisfaction in predicting job burnout in teachers of students with special needs in Shiraz, Iran. The sample included 136 teachers of students with special needs that were selected through convenience sampling. For data collection, the Burnout Inventory, Job Stress Questionnaire, and the Minnesota Satisfaction Questionnaire were used. Data were analysed using Pearson correlation coefficient and simultaneous multiple regression. The results showed that job stress positively and significantly predicted job burnout and job satisfaction negatively and significantly predicted job burnout. According to the findings of this study, it is suggested that organisations related special education field to design and develop appropriate educational and supportive programs (such as holding workshops on stress management in the workplace, providing free counseling and psychological services, identifying individual and environmental factors affecting job satisfaction in teachers of students with special needs, helping to increase their job satisfaction, providing assistants for these teachers, and etc.). This will increase job satisfaction and reduce job stress in teachers of students with special needs. In this way, the burnout of teachers of students with special needs will be reduced.